Offshore Service Vessel activity forecast and regulatory modeling in the U.S. Gulf of Mexico, 2012–2017. (July 2015) - Kaiser, Mark J.
Abstract: Offshore support vessels (OSVs) have important economic and environmental impacts on coastal communities in the Gulf Coast region and these impacts depend on the quantity and spatial distribution of vessel activity, which in turn depends on the type and geographic distribution of exploration and development. In this paper, port activity is quantified according to offshore activity expected to arise from current and new lease sales categorized according to water depth, planning area, and vessel class. Between 53, 000 and 119, 000 trips per year are expected to be required to support exploration, development and production in the Gulf of Mexico from 2012 to 2017, and approximately half of all trips are expected to emanate from Port Fourchon, Louisiana, with the next largest port, Cameron, Louisiana, contributing an additional 14% of activity. During the 2012–2017 period, the majority of trips are expected to support shallow water production operations. Highlights: Between 53, 000 and 119, 000 trips per year are required to support exploration, development and production in the Gulf of Mexico from 2012 to 2017. Half of all OSV trips emanate from Port Fourchon, Louisiana. The next largest port, Cameron, Louisiana, contributes an additional 14% of OSV activity.